High-insulativity modified carbon black and preparation method thereof

By modifying the surface of carbon black with silane coupling agent and gester diborate, the problems of high conductivity and poor dispersion in insulating inks are solved, high insulation and good dispersion are achieved, and the performance consistency of the ink is improved.

CN119775803AActive Publication Date: 2025-04-08CHONGQING HANJI NEW MATERIAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411749013.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-08
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing carbon black has high electrical conductivity in insulating inks, which affects the insulating properties of the inks, and has poor dispersion in resins, resulting in inconsistent printing quality and insulation properties.

Method used

The carbon black surface modification is performed by using a silane coupling agent to form a physical barrier to prevent direct contact between the carbon black particles and introduce a gester diborate structure to enhance insulation properties.

Benefits of technology

The insulating properties of carbon black and dispersion in resin are significantly improved, ensuring uniformity of ink and consistency of ink performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775803A_ABST
    Figure CN119775803A_ABST
Patent Text Reader

Abstract

The invention discloses high-insulativity modified carbon black and a preparation method thereof, and belongs to the technical field of carbon black modification. The preparation method comprises the following steps: firstly, pretreating the surface of the carbon black by using organic acid to improve active oxygen groups on the surface of the carbon black, and then treating the carbon black by using a silane coupling agent containing an isocyanurate structure. The silane coupling agent forms a physical barrier to hinder direct contact of carbon black particles, and the isocyanurate is stable in structure, uniform and compact in electron cloud distribution and capable of limiting a charge conduction path and remarkably improving the insulativity of the carbon black. In addition, gem-diborate is introduced to an allyl side group of diallyl isocyanurate, so that the arrangement among molecules is tighter and more ordered, electron migration channels are reduced, and the insulating property is enhanced. Meanwhile, gem-borate has high activity and polarity, is beneficial to dispersion of the modified carbon black in the resin, and is firmly combined on the resin through a plurality of action modes, so that the dispersity and stability of the modified carbon black in the resin are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon black modification, and in particular relates to a highly insulating modified carbon black and a preparation method thereof. Background Art

[0002] As an important industrial raw material, carbon black is widely used in many fields. Its unique structure and properties determine its performance and role in different fields. Carbon black is a nearly spherical nanoparticle composed of carbon elements, and its basic structural unit is a layer composed of six-membered rings. These layers are stacked in a disordered manner, forming a microcrystalline structure similar to graphite, but the microcrystals are smaller and irregularly arranged. There are a large number of pores and defects inside the carbon black particles, which gives it a high specific surface area. This special structure enables carbon black to interact strongly with other substances, but it is these characteristics that bring some challenges to its application.

[0003] There are partially delocalized π electrons in the carbon black microcrystalline structure, and these electrons can move to a certain extent, thereby conducting electric current. The conductivity of carbon black is related to factors such as its structure, particle size, and surface chemical properties. Generally speaking, the more developed the structure, the smaller the particle size, and the higher the surface activity of the carbon black, the better its conductivity. This is beneficial in some applications that require conductive properties, but it becomes a problem in many scenarios that require insulating properties. For example, in the application of insulating inks, the conductivity of carbon black will affect the insulating properties of the ink, which may cause problems such as short circuits between electronic components such as printed circuit boards, affecting the performance and reliability of electronic products.

[0004] The surface of carbon black has a high surface energy and is easy to agglomerate. At the same time, its surface contains some functional groups, such as carboxyl and hydroxyl groups. These functional groups may interact with each other, further causing the carbon black particles to aggregate together and making it difficult to disperse evenly in the resin. There are differences in the chemical structure and polarity of resin and carbon black, resulting in poor compatibility between them. It is difficult for resin molecules to fully infiltrate the surface of carbon black particles, making it easy for carbon black to form agglomerates in the resin, affecting the dispersion effect. This problem of poor dispersibility is also particularly prominent in insulating inks, which will lead to a decrease in the uniformity of the ink, affecting the consistency of printing quality and insulation performance. Therefore, in order to meet the needs of application fields with high requirements for insulation performance, such as insulating inks, it is necessary to modify carbon black, increase its insulation properties, and improve its dispersibility in the resin. Summary of the invention

[0005] In view of the above situation, in order to overcome the defects of the prior art, the present invention modifies the surface of carbon black by modifying the silane coupling agent, so that it has higher insulation and improves its dispersibility in the resin.

[0006] In order to achieve the above object, the following technical scheme is adopted: The present invention provides a method for preparing modified carbon black with high insulation properties, comprising the following steps:

[0007] S1. Add carbon black to organic acid, mix well and heat to 50°C, react for 5-8h, filter, and dry at 100-120°C for 8-12h to obtain pretreated carbon black;

[0008] S2, dissolving diallyl isocyanurate in toluene, adding triethylaluminum, bis(dibenzylideneacetone palladium, bis(pinacol)diboron and 2-adamantanone under the protection of nitrogen atmosphere, reacting at 80-100°C for 5-8h, filtering, evaporating the filtrate to dryness to obtain a modifier, adding allyltrimethoxysilane to dichloromethane under the protection of nitrogen atmosphere, adding the modifier once more, mixing evenly, reacting at room temperature for 2-5h, then removing dichloromethane under reduced pressure, adding the product to anhydrous ethanol, filtering, removing anhydrous ethanol under reduced pressure to obtain a modified silane coupling agent;

[0009] S3. Add the pretreated carbon black into a sand mill, then add the modified silane coupling agent solution, heat to 50-80° C., sand mill for 10-18 hours, then filter, and dry at 100-120° C. for 8-12 hours to obtain highly insulating modified carbon black.

[0010] Furthermore, the particle size of the carbon black is 100-200 nm.

[0011] Furthermore, the organic acid is one of tannic acid, hydroxyethylidene diphosphonic acid and dithiol dihydroxyacetic acid.

[0012] Furthermore, in step S1, the mass ratio of carbon black to organic acid is 1:40-60.

[0013] Furthermore, in the step S1, the mass ratio of diallyl isocyanurate, toluene, triethylaluminum, bis(dibenzylideneacetone palladium), bis(pinacol)diboron and 2-adamantanone is 1:80-120:0.05-0.2:0.02-0.05:1.2-1.5:1-3.

[0014] Furthermore, in step S1, the mass ratio of allyltrimethoxysilane, dichloromethane, modifier and anhydrous ethanol is 1:5-10:0.8-1:10-15.

[0015] Furthermore, in step S3, the feed mass ratio of the pretreated carbon black to the modified silane coupling agent solution is 1:20-35.

[0016] Furthermore, the silane coupling agent solution is a solution obtained by mixing a modified silane coupling agent with methanol or ethanol in a mass ratio of 1:1.5-1:2.5.

[0017] The invention also provides a highly insulating modified carbon black, which is prepared by the preparation method.

[0018] The beneficial effects of the present invention are:

[0019] (1) The present invention firstly performs surface pretreatment on carbon black by using organic acid to increase the active oxygen groups on the surface of carbon black, and then performs surface treatment on carbon black by using a silane coupling agent containing an isocyanurate structure. The silane coupling agent forms a physical barrier, which effectively hinders the direct contact between carbon black particles, thereby improving the insulation of carbon black. The isocyanurate structure has a six-membered heterocyclic structure, which is stable in structure. The electron cloud distribution in the molecule is relatively uniform and compact, making it difficult for the charge to be transferred within and between molecules, greatly limiting the charge conduction path, thereby significantly improving the insulation of carbon black.

[0020] (2) The present invention also introduces geminal diborates on the two allyl side groups of diallyl isocyanurate, which further enhances the performance of carbon black. The geminal diborates have a strong interaction force, which makes the molecular arrangement more compact and orderly, and can effectively reduce the migration channels of electrons in the material. Due to the presence of geminal diborates, these migration channels become narrower, which greatly limits the mobility of electrons and further enhances the insulation performance. At the same time, the activity and polarity of geminal borate are higher than those of single borate. When mixed with matrix materials such as resin, this high activity and polarity are conducive to better dispersion of modified carbon black in the resin, and facilitate the modified carbon black to be firmly bound to the resin material through various modes of action such as chemical bonding, hydrogen bonding and van der Waals force, thereby improving the dispersibility and stability of the modified carbon black in the resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The results of evaluating the fluidity of the modified carbon black in the resin of the present invention are as follows;

[0022] Figure 2 This is the OD value test result of the ink made from the modified carbon black of the present invention.

[0023] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0026] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0027] Example 1

[0028] A method for preparing highly insulating modified carbon black comprises the following steps:

[0029] S1. Add carbon black to organic acid, mix well and heat to 50°C, react for 5-8h, filter and dry at 100°C for 8h to obtain pretreated carbon black;

[0030] S2, dissolving diallyl isocyanurate in toluene, adding triethylaluminum, bis(dibenzylideneacetone palladium, bis(pinacol)diboron and 2-adamantanone under the protection of nitrogen atmosphere, reacting at 80°C for 5h, filtering, evaporating the filtrate to dryness to obtain a modifier, adding allyltrimethoxysilane to dichloromethane under the protection of nitrogen atmosphere, adding the modifier once more at once, mixing evenly, reacting at room temperature for 2-5h, then removing dichloromethane under reduced pressure, adding the product to anhydrous ethanol, filtering, and removing anhydrous ethanol under reduced pressure to obtain a modified silane coupling agent;

[0031] S3. Add the pretreated carbon black into a sand mill, then add the modified silane coupling agent solution, heat to 50° C., sand mill for 10 hours, then filter, and dry at 100° C. for 8 hours to obtain highly insulating modified carbon black.

[0032] The particle size of the carbon black is 100-200nm; the organic acid is tannic acid; the mass ratio of the carbon black and the organic acid in the step S1 is 1:40; the mass ratio of diallyl isocyanurate, toluene, triethylaluminum, bis(dibenzylideneacetone palladium), bis(pinacol)diboron and 2-adamantanone in the step S1 is 1:80:0.05:0.02:1.2:1; the mass ratio of allyltrimethoxysilane, dichloromethane, modifier and anhydrous ethanol in the step S1 is 1:5:0.8:10; the mass ratio of the pretreated carbon black and the modified silane coupling agent solution in the step S3 is 1:20; the silane coupling agent solution is a solution obtained by mixing the modified silane coupling agent with methanol or ethanol in a mass ratio of 1:1.5.

[0033] Example 2

[0034] A method for preparing highly insulating modified carbon black comprises the following steps:

[0035] S1, adding carbon black to organic acid, mixing evenly, heating to 50°C, reacting for 8 hours, filtering, and drying at 120°C for 12 hours to obtain pretreated carbon black;

[0036] S2, dissolving diallyl isocyanurate in toluene, adding triethylaluminum, bis(dibenzylideneacetone palladium, bis(pinacol)diboron and 2-adamantanone under the protection of nitrogen atmosphere, reacting at 100°C for 8h, filtering, evaporating the filtrate to dryness to obtain a modifier, adding allyltrimethoxysilane to dichloromethane under the protection of nitrogen atmosphere, adding the modifier once more at once, mixing evenly, reacting at room temperature for 5h, then removing dichloromethane under reduced pressure, adding the product to anhydrous ethanol, filtering, and removing anhydrous ethanol under reduced pressure to obtain a modified silane coupling agent;

[0037] S3. Add the pretreated carbon black into a sand mill, then add the modified silane coupling agent solution, heat to 80° C., sand mill for 18 hours, then filter, and dry at 120° C. for 12 hours to obtain highly insulating modified carbon black.

[0038] The particle size of the carbon black is 100-200nm; the organic acid is hydroxyethylidene diphosphonic acid; the mass ratio of the carbon black and the organic acid in the step S1 is 1:60; the mass ratio of diallyl isocyanurate, toluene, triethylaluminum, bis(dibenzylideneacetone palladium), bis(pinacolato)diboron and 2-adamantanone in the step S1 is 1:120:0.2:0.05:1.5:3; the mass ratio of allyltrimethoxysilane, dichloromethane, modifier and anhydrous ethanol in the step S1 is 1:10:1:15; the mass ratio of the pretreated carbon black and the modified silane coupling agent solution in the step S3 is 1:35; the silane coupling agent solution is a solution obtained by mixing the modified silane coupling agent with methanol or ethanol in a mass ratio of 1:2.5.

[0039] Example 3

[0040] A method for preparing highly insulating modified carbon black comprises the following steps:

[0041] S1. Add carbon black to organic acid, mix well and heat to 50°C, react for 5-8h, filter, and dry at 110°C for 10h to obtain pretreated carbon black;

[0042] S2, dissolving diallyl isocyanurate in toluene, adding triethylaluminum, bis(dibenzylideneacetone palladium, bis(pinacol)diboron and 2-adamantanone under the protection of nitrogen atmosphere, reacting at 90°C for 6h, filtering, evaporating the filtrate to dryness to obtain a modifier, adding allyltrimethoxysilane to dichloromethane under the protection of nitrogen atmosphere, adding the modifier once more, mixing evenly, reacting at room temperature for 3.5h, then removing dichloromethane under reduced pressure, adding the product to anhydrous ethanol, filtering, removing anhydrous ethanol under reduced pressure to obtain a modified silane coupling agent;

[0043] S3. Add the pretreated carbon black into a sand mill, then add the modified silane coupling agent solution, heat to 60° C., sand mill for 12 hours, then filter, and dry at 110° C. for 10 hours to obtain highly insulating modified carbon black.

[0044] The particle size of the carbon black is 100-200nm; the organic acid is dithiol dihydroxyacetic acid; the mass ratio of carbon black and organic acid in step S1 is 1:50; the mass ratio of diallyl isocyanurate, toluene, triethylaluminum, bis(dibenzylideneacetone palladium), bis(pinacol)diboron and 2-adamantanone in step S1 is 1:100:0.1:0.03:1.3:2; the mass ratio of allyltrimethoxysilane, dichloromethane, modifier and anhydrous ethanol in step S1 is 1:7.5:0.9:12; the mass ratio of pretreated carbon black and modified silane coupling agent solution in step S3 is 1:25; the silane coupling agent solution is a solution obtained by mixing the modified silane coupling agent with methanol or ethanol in a mass ratio of 1:2.

[0045] Comparative Example 1

[0046] The difference between this comparative example and Example 3 is that an equal amount of allyltrimethoxysilane is used to replace the modified silane coupling agent, and the rest is the same as Example 3.

[0047] Comparative Example 2

[0048] The difference between this comparative example and Example 3 is that an equal amount of diallyl isocyanurate is used to replace the modifier, and then reacted with allyltrimethoxysilane. The rest is the same as Example 3.

[0049] Test Example 1

[0050] Evaluation of insulation properties of modified carbon black

[0051] The modified carbon black prepared in each embodiment and comparative example was made into ink according to the following components, and then the insulation property of the ink was analyzed. The ink included the following components in parts by weight: 30 parts of ES120 saturated polyester resin, 3 parts of BYK-168 dispersant, 10 parts of modified carbon black, 50 parts of ethyl acetate, and 0.5 parts of fumed silica matting powder.

[0052] The control group used unmodified carbon black instead of modified carbon black, and ink was prepared according to the above components. The ink of each embodiment, comparative example and control group was coated on a glass substrate plated with ITO. The surface resistance was tested after curing. The results are shown in Table 1.

[0053] It can be seen from the results in Table 1 that the surface resistance values ​​of each group of the embodiments are extremely high, indicating that they have excellent insulation properties. This is because the present invention performs surface pretreatment on carbon black by using an organic acid to increase the active oxygen groups on the surface of carbon black, and then performs surface treatment on carbon black by using a silane coupling agent containing an isocyanurate structure. The silane coupling agent forms a physical barrier, which effectively hinders the direct contact between carbon black particles and improves the insulation of carbon black. The isocyanurate structure has a stable six-membered heterocyclic structure, and the electron cloud in the molecule is evenly and tightly distributed, which limits the charge conduction path and significantly improves the insulation. At the same time, the introduction of geminal diborates on the two allyl side groups of diallyl isocyanurate further enhances the insulation performance. The interaction force between geminal diborates makes the molecules arranged tightly and orderly, reduces the electron migration channel, and greatly limits the mobility of electrons.

[0054] In Comparative Example 1, an equal amount of allyltrimethoxysilane is used instead of the modified silane coupling agent, and key components such as isocyanurate structure and geminal diborate are missing, resulting in a significant decrease in insulation performance. This shows that the special structure in the modified silane coupling agent is crucial to improving the insulation of carbon black. In Comparative Example 2, an equal amount of diallyl isocyanurate is used instead of the modifier to react with allyltrimethoxysilane. Since an effective modifier is not formed through a specific modification process, its insulation performance is also much lower than that of the embodiment. The control group is not modified with carbon black, and its original carbon black structure and properties make it easier to conduct charges, so the insulation performance is the worst.

[0055] Table 1 Evaluation results of insulation properties of modified carbon black

[0056] project Surface resistance / Ω Example 1 <![CDATA[1.55×10 16 ]]> Example 1 <![CDATA[1.52×10 16 ]]> Example 1 <![CDATA[1.62×10 16 ]]> Comparative Example 1 <![CDATA[4.58×10 11 ]]> Comparative Example 2 <![CDATA[1.78×10 10 ]]> Control group <![CDATA[7.32×10 7 ]]>

[0057] Test Example 2

[0058] Evaluation of the fluidity of modified carbon black in resin

[0059] The viscosity of each group of ink prepared in Test Example 1 was tested, and the results are shown in Figure 1 .

[0060] Depend on Figure 1It can be seen from the results that in the modification process of the embodiment, the activity and polarity of the geminal borate are relatively high. When the modified carbon black is mixed with the resin, the geminal borate can interact with the resin molecules through a variety of interaction modes. On the one hand, it can form a strong chemical bond with the resin molecules. This chemical bonding enables the modified carbon black to be firmly bound to the resin molecular chain and plays a certain connecting and supporting role between the molecular chains, which is conducive to forming a relatively stable and uniform dispersion system. On the other hand, there are weaker interactions such as hydrogen bonding and van der Waals forces between the geminal borate and the resin molecules. The synergistic effect of these multiple interactions enables the modified carbon black to be evenly dispersed in the resin, reducing the occurrence of agglomeration.

[0061] In Comparative Example 1, an equal amount of allyltrimethoxysilane was used to replace the modified silane coupling agent, and in Comparative Example 2, an equal amount of diallyl isocyanurate was used to replace the modifier to react with allyltrimethoxysilane. In these two cases, the modification effect of the carbon black surface was different from that in the examples. This may be because the high activity and polarity of the geminal borate are missing, or the structural change of the modifier leads to a weakened interaction with the resin. Without a suitable modifier structure, carbon black is more likely to agglomerate in the resin. The agglomerated carbon black particles will increase the internal friction of the ink system, making the relative movement between molecules difficult, thereby resulting in increased viscosity and poor fluidity.

[0062] The unmodified carbon black surface has poor compatibility with the resin and lacks effective surface modification and interaction mechanisms as in the examples. The interaction between the functional groups on the surface of the unmodified carbon black and the resin molecules is weak, making it difficult to disperse evenly in the resin and easily forming larger agglomerates.

[0063] Test Example 3

[0064] OD value of ink made from modified carbon black

[0065] The transmittance at 550nm was measured by a spectrophotometer, and the OD value of each group of inks prepared in Test Example 1 was tested. The results are shown in Figure 2 .

[0066] The modified carbon black prepared in the embodiment has good dispersibility in the resin. When light is irradiated to the ink system, the evenly dispersed carbon black particles can effectively scatter and absorb the light. Since the carbon black particles are evenly distributed, the scattering and absorption degrees of light of different wavelengths are relatively consistent, so that the transmittance at 550nm can be properly adjusted, thereby obtaining a better OD value. The good combination and uniform dispersion state between the modified carbon black and the resin also help to maintain the stability of the ink system. When light passes through, the transmittance will not change drastically due to local aggregation or separation of carbon black, thereby ensuring the stability and reliability of the OD value.

[0067] The carbon black in the comparative example is not well modified and is not evenly dispersed in the resin, while the unmodified carbon black is prone to agglomeration in the resin, and the size and distribution of the agglomerates formed are uneven. Therefore, the OD values ​​of the comparative example and the control group are not ideal.

[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0069] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing highly insulating modified carbon black, characterized in that: The steps include: S1. Add carbon black to organic acid, mix well and heat to 50°C, react for 5-8h, filter, and dry at 100-120°C for 8-12h to obtain pretreated carbon black; S2, dissolving diallyl isocyanurate in toluene, adding triethylaluminum, bis(dibenzylideneacetone palladium, bis(pinacol)diboron and 2-adamantanone under the protection of nitrogen atmosphere, reacting at 80-100°C for 5-8h, filtering, evaporating the filtrate to dryness to obtain a modifier, adding allyltrimethoxysilane to dichloromethane under the protection of nitrogen atmosphere, adding the modifier once more, mixing evenly, reacting at room temperature for 2-5h, then removing dichloromethane under reduced pressure, adding the product to anhydrous ethanol, filtering, removing anhydrous ethanol under reduced pressure to obtain a modified silane coupling agent; S3. Add the pretreated carbon black into a sand mill, then add the modified silane coupling agent solution, heat to 50-80° C., sand mill for 10-18 hours, then filter, and dry at 100-120° C. for 8-12 hours to obtain highly insulating modified carbon black.

2. The method for preparing the highly insulating modified carbon black according to claim 1, characterized in that: The particle size of the carbon black is 100-200 nm.

3. The method for preparing the highly insulating modified carbon black according to claim 2, characterized in that: The organic acid is one of tannic acid, hydroxyethylidene diphosphonic acid and dithiol dihydroxyacetic acid.

4. The method for preparing the highly insulating modified carbon black according to claim 3, characterized in that: In step S1, the mass ratio of carbon black to organic acid is 1:40-60.

5. The method for preparing the highly insulating modified carbon black according to claim 4, characterized in that: In the step S1, the feed mass ratio of diallyl isocyanurate, toluene, triethylaluminum, bis(dibenzylideneacetone palladium), bis(pinacol)diboron and 2-adamantanone is 1:80-120:0.05-0.2:0.02-0.05:1.2-1.5:1-3.

6. The method for preparing the highly insulating modified carbon black according to claim 5, characterized in that: In the step S1, the mass ratio of allyltrimethoxysilane, dichloromethane, modifier and anhydrous ethanol is 1:5-10:0.8-1:10-15.

7. The method for preparing the highly insulating modified carbon black according to claim 6, characterized in that: In the step S3, the feed mass ratio of the pretreated carbon black to the modified silane coupling agent solution is 1:20-35.

8. The method for preparing the highly insulating modified carbon black according to claim 7, characterized in that: The silane coupling agent solution is a solution obtained by mixing a modified silane coupling agent with methanol or ethanol in a mass ratio of 1:1.5-1:2.

5.

9. A highly insulating modified carbon black, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Surface-modified carbon black and dispersions thereof

    CN101326247A

  • Method for preparing carbon black nano material

    CN106752119A

  • Rubber material containing polyborosiloxane and preparation method thereof

    CN116284797A

  • Modified carbon black, photosensitive black resin composition and black matrix resist composition for colored filter

    JP2002371204A

  • Carbon black pigment, its dispersion material and manufacturing method

    JP2007212697A

Cited By

  • High-thermal-conductivity carbon black as well as preparation method and application thereof

    CN120158117A